The benefits of active transportation interventions: A review of the evidence - Dillon Fitch-Polse; Swati Agarwal (Journal of Transport and Land Use)
Interventions to promote active travel (walking and bicycling) have manifold societal benefits. This study reviews the benefits of active travel infrastructure (e.g., painted bicycle lane, pedestrian refuge island) and programmatic interventions (e.g., bike share program), synthesizes the effects by outcome categories and provides a summary of the effects, and quantifies the effects where possible. We cite 236 studies on intervention-specific findings. Additional evidence is used to synthesize the benefits of active travel interventions into different benefit categories including safety, physical activity, reduction in vehicle miles traveled and emissions, other health effects, and economic activity. There is relatively more evidence in the literature on safety effects and changes in bicycling and walking associated with active transportation interventions than on other effects such as changes in physical activity and vehicle miles traveled. In general, we find strong evidence for wide ranging societal benefits from active transportation interventions that increase public health and transportation system sustainability in cost-effective ways. Variation in effects is substantial for most infrastructure interventions, likely due to the wide variety of land use, environmental, cultural, and political contexts, as well as the wide variety of research methods and analyses employed across a diverse set of academic fields. The existing local transportation infrastructure and land-use patterns are especially likely to moderate the effects of active transportation interventions. This suggests that it is necessary to keep the local context in mind when evaluating the effects of specific interventions.